An experimental study of the effects of curtain fabrics as heat insulators - Ureta, Sarah Catherine T.
The study investigated how curtain fabrics can affect the temperature levels in a given bedroom. The use of curtains is a favorable way of reducing heat in a room without changing its structure. The study aimed to compare the efficiency of curtain fabrics in barring heat from a certain space. The first fabric tested was a cotton-silk fabric, the second fabric used was an acrylic-polyester fabric, and the third fabric was rayon and cotton. All fabrics varied in openness. An experimental method was used in the research. An experiment set-up for eight days was conducted, and the final results recorded in a chart. Three thermometers were placed at specific points in the room, the Outside Thermometer, a Central Thermometer, an End Room Thermometer. A small survey was conducted to evaluate comfort levels among respondents. The data gathered was analyzed through comparing the differences between the outside and inside temperatures, measuring the variances of temperatures between all studies, computing for the mode temperature for each study in order to compare them with the standard Comfortable Temperature, and organizing into pie charts per survey question the responses of those involved in the survey. The research was successful in proving that curtain fabrics can reduce heat by a certain margin. Of the three, the acrylic-polyester fabric was the most effective. Even so, the reduction of heat inflow does not guarantee comfort. The survey results and the comparison with the standard Comfortable Temperature show this. In the cotton-silk study, the far end of the wall was proved to have a higher temperature than the center of the room, as opposed to the other fabrics.